Stimuli-Responsive Hydrogels for Controlled Drug Delivery in Oncology: A Comprehensive Review - Muhammad Irfan Siddique, (Asian Journal of Pharmaceutics (AJP), 2025)
Advancements in cancer treatment have been significant, but challenges remain with traditional methods such as chemotherapy and radiation, which often suffer from poor specificity, toxicity, and drug resistance. This highlights the need for more targeted drug delivery systems. On-demand, stimuli-responsive hydrogels offer a promising solution, capable of releasing drugs in response to biological signals from the tumor microenvironment. However, clinical challenges such as biocompatibility, scalability, and regulatory constraints still hinder their widespread adoption. This review explores hydrogels that react to pH, temperature, and enzyme activity–key traits of cancerous tissues. These “smart” materials improve drug bioavailability, reduce off-target effects, and enhance patient responses. We also discuss advanced hydrogels with multiple responsive elements, helping counteract drug resistance. While these hydrogels are transforming cancer therapy, challenges such as biocompatibility, scalability, and regulatory hurdles persist. Future directions may leverage emerging technologies such as artificial intelligence to optimize hydrogel design, paving the way for safer, more effective, and personalized treatments.